Efficient detoxication of hydroxylamine and nitrite through heterotrophic nitrification and aerobic denitrification by Acinetobacter johnsonii EN-J1 - Zhang, Manman; He, Tengxia; Wu, Qifeng; Chen, Mengping (Frontiers in Microbiology, 2023)
The roles of hydroxylamine (NH2OH) and nitrite (NO2--N) in accelerating the elimination of multiple nitrogen sources by a novel isolated strain of Acinetobacter johnsonii EN-J1 were investigated in this study. The results demonstrated that strain EN-J1 could eliminate 100.00% of NH2OH (22.73 mg/L) and 90.09% of NO2--N (55.32 mg/L), with maximum consumption rates of 1.22 and 6.75 mg/L/h, respectively. Prominently, the toxic substances NH2OH and NO2--N could both facilitate nitrogen removal rates. Compared with the control treatment, the elimination rates of nitrate (NO3--N) and NO2--N were enhanced by 3.44 and 2.36 mg/L/h after supplementation with 10.00 mg/L NH2OH, and those of ammonium (NH4+-N) and NO3--N were improved by 0.65 and 1.00 mg/L/h after the addition of 50.00 mg/L NO2--N. Furthermore, the nitrogen balance results indicated that over 55.00% of the initial total nitrogen was transformed into gaseous nitrogen by heterotrophic nitrification and aerobic denitrification (HN-AD). Ammonia monooxygenase (AMO), hydroxylamine oxidoreductase (HAO), nitrate reductase (NR) and nitrite reductase (NIR), which are essential for HN-AD, were detected at levels of 0.54, 0.15, 0.14 and 0.01 U/mg protein, respectively. All findings confirmed that strain EN-J1 could efficiently execute HN-AD, detoxify NH2OH and NO2--N, and ultimately promote nitrogen removal rates.